Burden sharing and cohesion countries in European climate policy: The Portuguese example - Suraje Dessai; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2000)
The EU has been a leader in international climate policy. However, due to activities of interest groups, domestic action, an area which the EU has strongly defended, is proving difficult to carry out, particularly for cohesion member states. Although their behaviour resembles free-riding, at least in an international dimension, Cohesion country targets are actually challenging in the face of their economic boom. Portugal accepted accepted limiting its GHGs emissions to a 27% increase up to 2010 whereas current projections lead to doubt that Portugal is capable of achieving its target unless more stringent policies are implemented. Underdeveloped institutional capacities and lack of abatement interests accompanied by the rapid economic and road traffic growth are the main causes of the inefficiency of current "quasi-policies". If Portugal is unable to comply, a consistent EU-wide climate policy is impossible and the risk that the EU as a whole fails to reach its Kyoto targets rises considerably. To reduce this risk, the EU could try to introduce strong enforcement rules and sanctions to prevent member states overshooting their targets. This will be extremely difficult as past efforts to enforce EU regulation have shown. A second way may be to use EU enlargement to enlarge the bubble by the accession countries and thus gain a safety margin. The third and easiest way would be to give the EU Commission the power to buy emission permits from abroad if the target is not reached and reduce EU transfers to those countries that have not reached their target proportionally to their degree of nonattainment. This would open a safety valve while leaving an incentive to countries not to default on their target. Even if the EU manages to keep its bubble intact, Portugal represents the problem of future high emitters which will be followed by developing countries in the near future. Moreover, Portugal also represents an equity dilemma vis-?-vis developing nations as it will be difficult to ask the latter to limit their emissions when a developed country such as Portugal will have them increased. – – Die EU hat bislang eine führende Rolle in der internationalen Klimapolitik eingenommen. Allerdings ist die von der EU betonte Umsetzung heimischer Emissionsverringerungsmaßnahmen gegen den Widerstand mächtiger Interessengruppen nur schwer durchsetzbar, insbesondere für Kohäsionsländer. Obwohl die Emissionsziele dieser Länder international eher als Beleg für Freifahrerverhalten gesehen werden, sind sie angesichts des ökonomischen Aufschwungs ehrgeizig. Portugal akzeptierte die Begrenzung seines Treibhausgaswachstums auf 27% bis 2010. Jedoch zeigen aktuelle Prognosen, dass die Zielerreichung zweifelhaft ist, sofern nicht wirksamere Politiken eingeführt werden. Unterentwickelte Institutionen und das Fehlen von Interessengruppen, die von Emissionsverringerung profitieren, gehen mit starkem Wirtschafts- und Verkehrswachstum einher und sind Hauptgrund der Ineffizienz der derzeitigen "Quasi-Politik". Wenn Portugal sein Ziel nicht erreicht, wird eine konsistente EU-Klimapolitik unmöglich und das Risiko nimmt zu, daß die EU ihr Kyoto-Ziel nicht erreicht. Es könnte durch die Einführung strenger Sanktionen gegenüber Mitgliedsstaaten, die ihre Ziele verfehlen, reduziert werden. Allerdings zeigen Erfahrungen mit der Durchsetzung von EU-Regeln, daß dies mit erheblichen Schwierigkeiten verbunden ist. Eine zweite Möglichkeit ist die Nutzung der EU-Erweiterung zur Erweiterung der Emissionsgemeinschaft, die damit eine Sicherheitsreserve gewinnen würde. Die dritte und einfachste Möglichkeit wäre, der EU-Kommission die Möglichkeit einzuräumen, Emissionsrechte einzukaufen, falls das Ziel nicht erreicht wird. Die Finanzierung würde durch die Reduzierung von EU-Transfers an die Länder erfolgen, die ihr Ziel nicht erreicht haben. Eine derartige, proportionale Transferverringerung würde einen Anreiz schaffen, das Ziel zu erreichen. Selbst wenn die EU-Zielgemeinschaft intakt bleibt, zeigt Portugal das Problem zukünftiger Großemittenten auf, das für Entwicklungsländer relevant werden wird. Darüber hinaus gibt es auch ein Gerechtigkeitsproblem: wie können Entwicklungsländer überzeugt werden, ihre Emissionen zu verringern, wenn selbst Industrieländer wie Portugal sie erhöhen dürfen?
Keywords: 330; Klimaschutz; Wirtschaftliche Anpassung; Internationaler Transfer; EU-Staaten; Portugal; Kohäsion